Reuse of lime mud waste as filler in gypsum composites - Tolosa, Gabrieli Roefero [UNESP]; Souza, Saulo Vinicius Martins [UNESP]; Bacarin, Giovani Boaventura [UNESP]; Cabrera, Flávio Camargo [UNESP]; Job, Aldo Eloizo [UNESP] (Emerald, 2021)
Eco-efficient construction has emerged as a distinct new field. The reuse or recycling of residues for production of building materials has the potential to avoid incorrect disposal, decrease the volume of waste in landfills and reduce the extraction of natural resources, which deplete the environment. This study proposes a new approach to reuse lime mud (LM), mainly composed of calcium carbonate, as filler in gypsum plaster to replace gypsum in proportions of 5, 15 and 25%, tested after 7, 14 and 21 days. An elemental analysis of the residue showed calcium-rich composition and that the particle distribution was between 1 and 11 μm with a mean particle diameter around 6 μm. The density of gypsum/lime mud (G/LM) composites was reduced from gypsum (1244.9 kg/m3) to G/LM25 (1132.1 kg/m3) in 21 days. The flexural strength of gypsum after 21 days was 5.7 MPa compared to 5.4 MPa for G/LM5 (LM at 5%), the latter being a reduction of only 5.3% from the former. Even with incorporation of 25% of LM, after 21 days composites presented mechanical resistance above the standard international recommendations: compressive strength of 9.6 MPa (≥8.3 MPa recommended), axial compression strength of 8.5 MPa (≥6.0 MPa) and flexural strength of 3.7 MPa (≥2.0 MPa).
Keywords: Composite structures; Recycling & reuse of materials; Waste management & disposal